Work Behavior Analysis Of Customer Attitude Through The State Of The Working Environment At Kopiman Coffe Shop - Satriya Dwi Pangestu; Amanda Silviana; Deis Anggit D; Honorata Ratnawati Dwi Putranti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Employee work behaviour is greatly influenced by various kinds of customer attitudes and actions, both positive and negative. In general, a positive attitude from customers will provide indirect encouragement to improve performance. This research aims to analyze how employees' work behaviour relates to various customer attitudes, both positive and negative. This research method uses qualitative methods. The collection technique for this research was interviews with cafe managers and employees. The data obtained is based on information from management and various existing literature. The results of this research refer to how much customer attitudes influence how employees behave. Employees carry out duties and obligations according to the manager's direction. Of course, some of the directions that have been given could have gone better due to customers' attitude in the work environment. Thus, partially, there will be a significant influence between work behaviour and customer attitudes in the work environment.